Pengaruh Drama Korea Terhadap Cara Berkomunikasi Pada Mahasiswa Fakultas Dakwah Angkatan 2022 - Ridatasa Nadiawita; Nazwa Sabila Febiana; Minati Nurhidayah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research explores the influence of Korean dramas on the communication styles of students from the Faculty of Da'wah, specifically the 2022 cohort. Drawing on communication theory and cultural studies, the study investigates the impact of Korean dramas on interpersonal communication, non-verbal cues, and language use among the mentioned group. Through surveys and interviews, the research identifies key communication patterns influenced by exposure to Korean dramas, shedding light on the integration of Korean cultural elements into the communication practices of these students. The findings contribute to understanding the role of popular media in shaping communication norms within diverse cultural contexts, emphasizing the need for media literacy and cultural sensitivity in contemporary education.